Yogic Attitude For A Disciplined Way of Life - Divya , R (International Research Journal of Ayurveda & Yoga, 2021)
Yoga is considered to be a practical science which can teach human beings to control the mind and emotions as well. It is a way of life that provides a rare opportunity to leave the madness of the world behind and attain inner peace. Yoga is the exact mind- body medicine and is one of the greatest treasures of the unique Indian cultural heritage. Yogic lifestyle, yogic diet, yogic attitude and various yogic practices helps us to strengthen ourselves and develop positive health. Yoga has been recognized since then as a psychotherapy for the preventive and curative aspects of different disease conditions. This is more evident when we realize that yoga enables us to adopt right attitudes towards our problems and thus tackle them effectively in a wise manner. This article tries to describe the role of yogic attitude in promoting health, relieving stress and in turn to develop a positive health and wellbeing.